Investigation of the regulatory mechanisms of Guiqi Yimu Powder on dairy cow fatty liver cells using a multi-omics approach - Li, Chenlei; Wang, Feifei; Ma, Yanfen; Wang, Wenjia; Guo, Yansheng (Frontiers in Veterinary Science, 2024)
IntroductionFatty liver disease in dairy cows is a metabolic disorder that significantly affects their health and productivity, imposing a notable economic burden on the global dairy industry. Traditional Chinese medicine (TCM), characterized by its multi-component and multi-target features, has shown unique advantages in the prevention and treatment of various diseases. Guiqi Yimu Powder, a traditional TCM formula, enhances growth, boosts production efficiency, and strengthens immune function in livestock by regulating antioxidant along with anti-inflammatory pathways. However, its specific regulatory mechanisms on fatty liver in dairy cows remain unclear. This study aims to investigate the molecular-level effects and potential regulatory mechanisms of Guiqi Yimu Powder in a Trimethylamine N-oxide (TMAO) induced fatty liver cell model of dairy cows.MethodsWe employed a comprehensive analysis integrating transcriptomics, proteomics, metabolomics, and network pharmacology. An in vitro dairy cow fatty liver cell model was established using TMAO to induce lipid accumulation. Cells were treated with the optimal TMAO concentration identified through preliminary experiments, and further divided into a lipid accumulation group and Guiqi Yimu Powder treatment groups. The treatment groups received varying concentrations of Guiqi Yimu Powder (10, 20, 30, 40, or 50 g/L). High-throughput omics sequencing technologies were utilized to perform a comprehensive analysis of the treated cells. Bioinformatics methods were applied to explore the regulatory effects, aiming to elucidate the specific impacts of Guiqi Yimu Powder on lipid metabolism, liver function, and related signaling pathways, thereby providing scientific evidence for its potential application in the prevention and treatment of fatty liver in dairy cows.ResultsGuiqi Yimu Powder treatment significantly affected 1,536 genes, 152 proteins, and 259 metabolites. KEGG enrichment analysis revealed that the significantly altered molecules are involved in multiple pathways related to the pathology of fatty liver, including metabolic pathways, glutathione metabolism, hepatitis B, and AMPK signaling pathway (p < 0.05). Notably, joint analysis highlighted the regulatory mechanisms of Guiqi Yimu Powder on glutathione cycling, with L-5-Oxoproline identified as an important metabolic compound. These findings indicate its impact on oxidative stress, energy metabolism, and liver function, suggesting potential therapeutic applications for fatty liver in dairy cows.DiscussionThis study elucidated the regulatory mechanisms of Guiqi Yimu Powder on fatty liver cells in dairy cows, providing new scientific evidence for its potential application in the prevention and treatment of fatty liver disease.